2020
DOI: 10.26480/bdwre.01.2020.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment of Heavy Metals Due to Untreated Wastewater Irrigated Vegetables

Abstract: The present research study was conducted on Health risk assessment of heavy metals due to untreated wastewater irrigated vegetables in Faisalabad city. Samples of soil, groundwater, wastewater and vegetables were collected from different regions of the city where wastewater irrigation was in practice. The ground water and wastewater samples were analyzed for all the basic physical and chemical parameters and heavy metals like (Nickel, Lead, Cadmium, Zinc, Copper and Chromium). Most of the chemical parameters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In this study, the highest PLI found (0.36) was below 1, indicating that overall pollution of trace metals in the investigated samples was absent, but the I geo and CF have shown that the contamination potential for Cd, Cu, and Ni was moderate to strong, as displayed in Tables 7 and 8. In Pakistan, the human and environmental impacts of toxic metal concentrations, including in vegetables originating from untreated wastewater, remain a challenging matter in terms of research studies, food quality, food safety, and sustainability [63].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the highest PLI found (0.36) was below 1, indicating that overall pollution of trace metals in the investigated samples was absent, but the I geo and CF have shown that the contamination potential for Cd, Cu, and Ni was moderate to strong, as displayed in Tables 7 and 8. In Pakistan, the human and environmental impacts of toxic metal concentrations, including in vegetables originating from untreated wastewater, remain a challenging matter in terms of research studies, food quality, food safety, and sustainability [63].…”
Section: Discussionmentioning
confidence: 99%
“…The cycle of hydrology specifies the collection of mechanisms that carry water flow via system. The hydrological process is determined by evaporation, which is severely affected by the system due to the high pollution of wetlands, oceans as well as rivers (Nawaz et al, 2020;Daud et al, 2017). The rainfall ratio to agriculture is 5 to 10%.…”
Section: Less Rainstormmentioning
confidence: 99%
“…Total dissolved solids were the aggregate of all organic and in-organic substances present in a liquid in ionized, molecular and suspended state. TDS were measured by TDS meter (Nawaz et al, 2020).…”
Section: Total Dissolved Solids (Tds)mentioning
confidence: 99%